Bad Loans and De Novo Banks: Evidence From Italy. (16th January 2015) - Ambrosio, Rachele Anna; Coccorese, Paolo
<x xml:space="preserve">Abstract</x> The existing empirical evidence suggests that there is a 'winner's curse' for banks entering new markets. Actually, it has been assessed that de novo banks generally experience higher bad loans rates than mature banks for about 10 years. We investigate whether this persistence has characterised the Italian banking industry in the period 1995–2010, and find that theory predictions are confirmed by empirical results only for popular and commercial banks, while new cooperative credit banks (CCBs) outperform compared to mature ones due to their distinctive presence and focus on local markets.